2015
DOI: 10.1039/c5mb00008d
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the cytotoxic effects induced by the organogold(iii) complex Aubipycin cisplatin-resistant A2780 ovarian cancer cells: further evidence for the glycolytic pathway implication

Abstract: aThe cellular alterations produced in cisplatin-resistant A2780 ovarian cancer cells (A2780/R) upon treatment with the cytotoxic organogold(III) complex Aubipy c were investigated in depth through a classical proteomic approach. We observed that A2780/R cell exposure to a cytotoxic concentration of Aubipy c for 24 hours results in a conspicuous number of alterations at the protein level that were carefully examined. Notably, we observed that several affected proteins belong to the glucose metabolism system fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The cells were sonicated (15 s) and protein extracts were clarified by centrifugation at 8000g, 4°C for 15 min. Proteins were precipitated following a chloroform/methanol protocol [ 69 ] and the protein pellets were resolved in a buffer containing 8 M urea, 4% (w/v) 3-cholamidopropyl dimethylammonium-1-propane sulfonate (CHAPS), 65 mM dithioerythritol (DTE). The protein concentration was determined by the standard Bradford method (Bio-Rad Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were sonicated (15 s) and protein extracts were clarified by centrifugation at 8000g, 4°C for 15 min. Proteins were precipitated following a chloroform/methanol protocol [ 69 ] and the protein pellets were resolved in a buffer containing 8 M urea, 4% (w/v) 3-cholamidopropyl dimethylammonium-1-propane sulfonate (CHAPS), 65 mM dithioerythritol (DTE). The protein concentration was determined by the standard Bradford method (Bio-Rad Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…They also studied the cytotoxicity of Aubipyc in cisplatin-resistant A2780 ovarian cancer cells. They found that this compound regulates glucose metabolism in tumor cells and significantly reduces lactate production through interaction with glycolytic enzymes such as aldolase C (ALDOC), LDHB, GAPDH, and PKM ( Gamberi et al, 2015 ). This gold (III) compound could therefore downregulate glucose metabolism in tumor cells.…”
Section: The Effects Of Gold Compounds On Glucose Metabolism In Tumorsmentioning
confidence: 99%
“…[21][22][23] Both Au(I) and (III) complexes have gained considerable interest over the years as anticancer agents with preferential targeting of mitochondria, 24 thioredoxin proteasome, and inducing endoplasmic reticulum stress. [24][25][26][27][28][29][30][31][32] Gold complexes with multifaceted target mechanisms to evade resistance pathways are attractive.…”
Section: Introductionmentioning
confidence: 99%